Empowering the Voice of Heritage: The Evolution and Impact of Tourist Guiding in Saudi Arabia - Yehia, Enas Fares (E-Journal of Tourism; Volume 11 Number 1 (March 2024), 2024)
This article explores the development of tourist guiding in Saudi Arabia, tracing its historical roots and analyzing the vital role guides play as cultural ambassadors and educators. It highlights the rigorous training and professional development programs that ensure guides are well-prepared to display Saudi heritage in a way that is both accurate and engaging. In this article, one of the most prominent focuses is on the empowerment and inclusion of women in the profession of tourist guiding. Further investigation into the influence of tourist guides on the preservation of cultural heritage and the promotion of sustainable tourism is presented in this article. Tourist guides are an essential component of the tourism ecosystem in Saudi Arabia, not only do they serve as guardians of cultural heritage, but they also play a significant role in Saudi Arabia's efforts to become a destination of choice for tourists from all over the world. Underscoring the transformative power of tourism that is directed by expertise, passion, and a profound dedication to heritage preservation is the role that they play in linking cultures and generating positive change.